Mapping the global literature output on nocturia: A bibliometric and visualized analysis. Issue 31 (5th August 2022) - Ahmad, Tauseef; Khan, Muhammad; Al-Omari, Basem
Abstract : Purpose: This study aims to facilitate researchers' and clinicians' understanding of research frontiers and trends in nocturia. It explores the scientific research outcomes and key bibliometric indices and plots global research on nocturia. Methods: A bibliometric retrospective study was designed, and an online search was conducted in the Web of Science Core Collection database using the potential search keywords related to nocturia in the title field with some specific filtration. HistCite™ and VOSviewer software for windows were used to analyze the data obtained for authors, journals, countries, institutions, keywords, and visualization mapping. Results: The initial search retrieved 1479 hits. A total of 1445 publications were included in the final analysis. Of these, 43.53% were published as articles. The most studied area in nocturia is urology nephrology. The most productive year was 2019 (n = 121, citations = 335), and the most prolific author, both in terms of publications (n = 97) and citations (1658) was Weiss JP. The most cited journal in nocturia research was the Journal of Urology (n = 293, citations = 3050). The most widely used keyword in nocturia publications was nocturia (n = 1249). Visualization mapping shows that the USA was the most influential and highly cited country in nocturia research. Conclusion: This study showed that there has been an increasing research trend in nocturia over the past few years. The current findings provide important empirical evidence for researchers, clinicians, and physicians to understand research frontiers and trends, achievements, collaborative networks, and hotspot research topics in the research field of nocturia.